Auster’s autobiographical ‘you’ in Report From the Interior: multi-faceted (inter)subjectivities - Sandrine SORLIN (E-REA)
This article focuses on the choice of the second-person pronoun in Paul Auster’s autobiographical work, Report from the Interior (2013). Unusual in the genre, this article demonstrates that it serves several functions within the economy of the narration but also across it (in its reaching out to the reader). Sliding between different potential referents as is the case in traditional “you novels,” the pronoun is always on the verge on merging into the first or third person pronoun, while assuming its addressivity at all times. Dislodging the ‘I’ from its egocentric position, it also enables different intersubjective frames to co-exist, in keeping with Auster’s conception of life-writing as inevitably fragmented and non-linear. As argued, the pronoun is a metaleptic “space-opener”, opening the autobiographer’s mental space for the reader to share as a “by-sider”: the second-person pronoun is what ensures an ethical encounter of selves in the dialectic of singularity and solidarity/shareability that Auster’s work fosters.